Reaching the unreachable: a mixed-method evaluation of multidimensional healthcare model addressing the healthcare service gaps in hard-to-reach Northern riverine Bangladesh - Md Refat Uz Zaman Sajib; Kamrul Hasan; Tanvir Hayder; A M Rumayan Hasan; Md. Musfikur Rahman; Saraban Ether; Atia Rahman; Tania Sultana Tanwi; Fariya Rahman; Abu Sayeed; Sanwarul Bari; Syed Moshfiqur Rahman; et al. (Archives of Public Health)
Abstract Background Hard-to-reach riverine communities of northern Bangladesh face unique challenges in healthcare services. Friendship, an international social purpose organization, implemented a 3-tier healthcare model addressing these unique challenges over the past 20 years. This study evaluated Friendship’s 3-tier healthcare model in the northern riverine area, assessing service-seeking practices, experiences, stakeholders’ perceptions, and cost benefits for beneficiaries. Methods A concurrent mixed-method approach was employed, including desk reviews, a cross-sectional quantitative survey, facility mapping, and qualitative interviews with service recipients, community representatives, healthcare providers, and health managers. Data were collected from five hard-to-reach riverine sub-districts across the Kurigram, Gaibandha, Bogura, Sirajganj, and Jamalpur districts of Bangladesh between April 2022 and July 2023. Data analysis followed major thematic domains for a comprehensive and complementary understanding. Results A significant proportion (43.0%) of survey participants had no formal education, were aged 18–35 (57.5%), and earned less than 1,620 USD yearly (66.6%). Friendship’s healthcare services at the doorstep through satellite clinics and Female Community Medic Aides were widely accepted and preferred within the community for convenience, affordability (0.05–0.09 USD service charges), and superior quality, particularly the specialized treatments available on the hospital ships. Conclusion Friendship’s 3-tier healthcare model made the accessibility and affordability of primary healthcare. Upon implementing a robust referral mechanism, continuing collaboration with the Government of Bangladesh, and expanding community awareness sessions to include topics such as mental health and disaster response, this model has the potential to be effective in similar settings in Bangladesh and other developing countries, as well as during emergency responses.